2017
DOI: 10.1002/jcop.21910
|View full text |Cite
|
Sign up to set email alerts
|

Interdependent self‐construal matters in the community context: Relationships of self‐construal with community identity and participation

Abstract: Two studies investigate the relationship between self‐construal (SC), community identity, and community participation among Chinese urban residents. Study 1 (n = 261) measured SC, community identity, and community participation behavior. Using cluster analysis, 4 distinct subgroups emerged: those with (a) independent SC, (b) interdependent SC, (c) dual SC, and (d) marginal SC. Results indicated that individuals in the interdependent SC subgroup reported higher community identity, particularly emotional identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…By contrast, doctors with a higher sense of identity will actively participate and play a mutually reinforcing role. This also validates previous study conclusions that the sense of identity in the community will increase individual participation [38]. From the perspective of social-capital theory, for doctors with lower interaction frequency, there should be a new section to increase the number of views and collections, thus increasing their sense of identity to maintain its existing users.…”
Section: Sense Of Identity In the Network Is Positively Related To Pasupporting
confidence: 89%
See 1 more Smart Citation
“…By contrast, doctors with a higher sense of identity will actively participate and play a mutually reinforcing role. This also validates previous study conclusions that the sense of identity in the community will increase individual participation [38]. From the perspective of social-capital theory, for doctors with lower interaction frequency, there should be a new section to increase the number of views and collections, thus increasing their sense of identity to maintain its existing users.…”
Section: Sense Of Identity In the Network Is Positively Related To Pasupporting
confidence: 89%
“…Physician title. ,10,15,16,17,30,33,37,38,41,43,45,50,51,52,54,55,57, 63, 64, 65, 67, 81, 82, 83, 85, 87, 90, 91, 92, 93, 94 …”
mentioning
confidence: 99%
“…Interdependent self‐construal was measured by using the self‐construal scale (SCS) developed by Singelis (1994). This SCS is one of the most well‐known measures of self‐construal and has been used in numerous top‐tier journal publications (Mass et al, 2019; Song & Lee, 2013; Steinmetz & Mussweiler, 2017; Xin et al, 2017). It is reported that independent self‐construal and interdependent self‐construal are orthogonal and coexist in individuals.…”
Section: Studymentioning
confidence: 99%
“…The literature shows that each individual possesses both of these self-construal. For example, a person could be high in both independent and interdependent self-construal (Cross et al, 2009(Cross et al, , 2011Gudykunst et al, 1996;Oetzel, 1998;Ren et al, 2013;Singelis, 1994;Xin et al, 2017). In other words, these two types of self-construal lead respectively to different behaviors in social communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation